DEVELOPMENT AND IN VITRO–IN VIVO EVALUATION OF GASTRORETENTIVE FLOATING TABLETS OF AN ANTIRETROVIRAL AGENT RITONAVIR - KIRAN R, SHIREESH; SHEKAR B, CHANDRA; BABU B, NAGENDRA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present research work concerns the development of the extended release of Ritonavir floating matrix tablets, designed to prolong the gastric residence time, increase the drug bioavailability, and diminish the side effects of irritating drugs. Methods: The floating tablets of Ritonavir were prepared by direct compression method using different grades of hydroxypropyl methylcellulose (HPMC), crospovidone, Polyox WSR 303, and sodium bicarbonate, as gas generating agent. Evaluation parameters and in vivo radiographic studies were conducted in suitable model. Results: Among all formulations, F21 was chosen as optimized formulation based on evaluation parameters such as floating lag time (33 s), total floating time (>24 h), and in vitro dissolution studies. From in vitro dissolution studies, the optimized formulation F21 and marketed product were shown 98.67% and 91.46±5.02% of drug release, respectively. The main appliance of medication discharge follows zero-order kinetics and non- Fickian transport by coupled diffusion and erosion. In vivo experiments maintained the potentials in extending the gastric residence time in the fasted state in beagle dogs. The mean gastric residence time of the optimized formulation found to be 330 min±40 in the stomach, where longer gastric residence time is an important condition for prolonged or controlled drug release and also for enhanced bioavailability. Conclusion: From in vitro and in vivo radiographic studies, Ritonavir floating tablets estimated to provide novel choice for harmless, inexpensive, and extended release for the effective management of AIDS.